Conflicting humours race, gender and national identity in Madam and Eve - Britten, Sarah (My University, 2016)
Madam & Eve is South Africa's most successful cartoon strip. Created by three white, middle class men, it has received praise both locally and overseas. At the same time, it has been the SUbject of very little published criticism. Comic strips are narratives which operate in specific ways, USing specific strategies to tell their stories. Analylis reveals several strategies through which Madam & Eve addresses the South African situation, for example, recasting Eurocentric CUltural phenomena in an indigenous mould. Following the cartoons from their inception in 1992 to the present reveals a narrative of the evolution of a national identity. Madam & Eve addresses an emblematic racial situation, that of the white madam and her black maid. But in tending to exclude men from its satire, it falls to examine gender roles ontically. A closer examination of the charge that Eve as an "icon of black femininity" is "oppressed" reveals that it is Madam who is the most stereotypical of the characters; there is a risk that this type of postcolonial criticism will itself slip into racism. Humour is, by its very nature, politically incorrect. It exposes the cracks in society and, in its opposition to authority, is profoundly democratic in orientation. In the context of South African humour, Madam & Eve steers a middle path between (white) conservative reaction and left-wing invective, Its brand of satire is too gentle to be truly subversive. For all its shortcomings, Madam & Eve deserve credit for addressing issues from a South African perspective. It encourages South Africans to laugh at issues that usually provoke anger. Humour is society's spety valve: in order for humour to change, society must change first. Those Who wish to see politically correct humour will have to create their own, and allow audiences to judge for themselves.
RESEARCH REPORT MA (by coursework)